Polyketides with antimicrobial activities from Penicillium canescens DJJ-1. (February 2023) - Wang, Jia-Peng; Shu, Yan; Zhang, Sheng-Qi; Yao, Lin-Lin; Li, Bing-Xian; Zhu, Li; Zhang, Xiao; Xiao, Huai; Cai, Le; Ding, Zhong-Tao
Abstract: Two undescribed polyketides canecines A-B, one unreported cyclopentenone canecine C, together with 12 known compounds were isolated from an extract of the fungus Penicillium canescens DJJ-1. Their structures were elucidated by detailed analysis of spectroscopic data, NMR calculations with d J -DP4 or DP4+, and their absolute configurations were further determined by quantum chemical calculations of ECD spectra or X-crystallography. Canecine A was a grisan polyketide featuring a dimethyltetrahydro-4 H -furo[2, 3- b ]pyran. Canecine A exhibited significant inhibitory activity against Candida albicans with an MIC value of 1 μg/mL and showed inhibitory effect on nitric oxide production in LPS-activated RAW264.7 macrophages. These results enrich the structural diversities of polyketides from endophytic fungi. Graphical abstract: Polyketides with antimicrobial activities from Penicillium canescens DJJ-1 of Aconitum brevicalcaratum Diels (Ranunculaceae). Image 1 Highlights: Three undescribed polyketides were isolated from Penicillium canescens DJJ-1. One compound showed antimicrobial activities. One compound showed inhibitory effects on LPS-induced NO production.